THE EFFECT OF PARENTAL INVOLVEMENT AND DIGITAL FINANCIAL LITERACY ON STUDENT LEARNING ACHIEVEMENT OF GRADE XI IN THE DIGITAL ERA AT SMKN 1 BOJONEGORO: PENGARUH KETERLIBATAN ORANG TUA DAN LITERASI KEUANGAN DIGITAL TERHADAP PRESTASI BELAJAR SISWA KELAS XI DI ERA DIGITAL DI SMKN 1 BOJONEGORO - DIANAWATI, DANI; Nur Rohman; Ali Mujahidin (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The purpose of this study was to partially and simultaneously test the influence of digital financial literacy and parental participation on students' learning success in the digital era at SMKN 1 Bojonegoro. This study used quantitative methodology and data collection using questionnaires. Of the 546 students involved in this study, 84 students were selected as samples. The data were tested using the SPSS version 25 computer program. The results showed that parental participation and digital financial literacy had a significant effect on students' learning success. The two independent variables did not have a simultaneous effect on students' learning success in the digital eraThe purpose of this study was to partially and simultaneously test the influence of digital financial literacy and parental participation on students' learning success in the digital era at SMKN 1 Bojonegoro. This study used quantitative methodology and data collection using questionnaires. Of the 546 students involved in this study, 84 students were selected as samples. The data were tested using the SPSS version 25 computer program. The results showed that parental participation and digital financial literacy had a significant effect on students' learning success. The two independent variables did not have a simultaneous effect on students' learning success in the digital era